Changes in Cognition and Hemodynamics 1 Year after Carotid Endarterectomy for Asymptomatic Stenosis - Košťál, Petr; Mrhálek, Tomáš; Kajanová, Alena; Bombic, Martin; Kubále, Jiří; Šterba, Luděk; Ostrý, Svatopluk; Fiedler, Jiří (Journal of Neurological Surgery Part A: Central European Neurosurgery, 2021)
Objectives The impact of a change in hemodynamics on cognitive skills in patients with asymptomatic carotid stenosis (ACS) after carotid endarterectomy (CEA) remains unclear. The aim of this study was to evaluate the results of CEA for ACS at 1 year by assessing the changes in anterior, middle, and posterior cerebral artery blood flow in tandem with changes in cognitive efficiency.Methods Flow volume in cerebral arteries using quantitative magnetic resonance angiography was measured in a group of 14 males and 5 females before and at 1 year after CEA for ACS. Cognitive efficiency was assessed by Repeatable Battery for the Assessment of Neuropsychological Status (RBANS). The values of flow volume were processed using simple ratio (SR) and were used for covariance analyses with changes in cognitive skills after CEA.Results A significant improvement in cognitive efficiency indexes of immediate memory and visuospatial perception at 1 year after CEA for ACS was observed. Simultaneously, a significant deterioration of speech index was noted. During the analysis of association between flow and cognition, the highest correlation could be seen between the middle cerebral artery (MCA) flow and the visuospatial perception. A change in posterior cerebral artery (PCA) flow was associated with an increase in immediate memory index and anterior cerebral artery (ACA) flow change with the speech index.Conclusion Convergence of data supporting the association between revascularization and cognitive improvement were added in a small, single-center cohort of ACS patients undergoing CEA. No significant differences in cognition were seen between preoperative findings and at 1 year after CEA. Visuospatial perception improvement was linked to flow change in MCA, immediate memory improvement to flow change in PCA, and speech index change to flow change in ACA. Methodical limitations of this small study preclude formulating larger generalizations. Hemodynamic factors in CEA should be assessed in a larger-scale study.
Keywords: carotid endarterectomy; carotid stenosis; cognitive dissonance; quantitative magnetic resonance angiography